Analysis of factors affecting BPJS patients in utilization of inpatient services in the city of Pematang Siantar Army Hospital - Alda Tertia Agripina Tarigan (Institute of Computer Science (IOCS), 2023)
BPJS is a legal entity formed to administer social security programs. BPJS Health participants can also be interpreted as consumers of health services. Hospitalization is a form of hospital health care services where sufferers stay or stay for at least one day. Utilization of health services is the result of the process of seeking health services by a person or group. The factors that influence BPJS patients in the utilization of inpatient services in this study are knowledge, attitudes, family income, health service facilities and the need for health services. The research design is a quantitative research using an analytical survey method and an explanatory research approach. out of 75 respondents there were 65 respondents (86%) the need factor affecting BPJS patients in the good category compared to 60 respondents (80%) predisposing factors affecting BPJS patients in the good category compared to 55 respondents (73%) supporting factors influencing BPJS patients in the good category for utilization inpatient services good category. The results of the analysis show that the probability value is (0.02) < sig_a = 0.05. The results of this analysis meet the criteria for the requirements of the relationship hypothesis, so it can be concluded that the analysis of the factors that influence BPJS patients in the utilization of inpatient services at the Pematangsiantar City Army Hospital is significant. The author's suggestion for this research is to add to the body of knowledge related to the factors that affect BPJS patients in the utilization of inpatient services.